Application of plackett-burman design to benzylation of o-cresol with benzyl alcohol (Bangladesh Journal of Scientific and Industrial Research, 2015)
Plackett-Burman design was employed to study the reaction of o-cresol with benzyl alcohol in the presence of anhydrous aluminium chloride as catalyst for screening variables. The variables chosen for the investigation were temperature, molar ratio of o-cresol to benzyl alcohol, amount of anhydrous AlCl3 catalyst (% by wt. of o-cresol), addition time (ta h), stirring time (ts h), stirring speed (rpm). Among these variables temperature, molar ratio of o-cresol to benzyl alcohol and amount of anhydrous AlCl3 were found to be important. A set of trials was planned according to a 3 factor 2-level Yates pattern experimental design with 2 replicates and the center point trial with 4 replicates. The critical response was the yield of benzyl o-cresol. Main effects as well as two- and three- factor interaction effects were statistically significant. A polynomial model was developed and the adequacy of the suggested model was checked up.Bangladesh J. Sci. Ind. Res. 50(3), 169-180, 2015